The politics and poetics of translation in Turkey 1923-1960 - Tahir Gürçağlar, Şehnaz. (Thesis (Ph.D.) - Bogazici University. Institute of Social Sciences, 2001., 2001)
Contemporary research on translation history in early republican Turkey is marked by a focus on the activities of the Translation Bureau [Tercüme Bürosu] (1940-1966) at the expense of other publishers which operated in various fields of translated literature. Şehnaz Tahir Gürçağlar's The Politics and Poetics of Translation in Turkey 1923-1960 challenges this focus and sets out to reveal the complex and diversified nature of the system of translated literature in the first four decades of the Republic. The study is carried out on two levels. On the broad level, the dissertation investigates the implications of the political transformation experienced in Turkey after the proclamation of the Republic for the cultural and literary fields, including the field of translated literature. On a more specific level, it holds translation under special focus and explores the discourse formed on translation and translators in speeches, articles, prefaces or books concentrating on such issues as the functions and definitions of translation, translation strategies and the translator's visibility. This is complemented by a descriptive study of a series of translated texts from the fields of both canonical and popular literature which investigates the norms (not) observed by translators throughout the 1920s-1950s with special emphasis on paratextual elements, approaches towards textual integrity, and the treatment of proper names and foreign cultural elements. The findings of the study suggest that the concepts of translation both affected and were affected by cultural processes in the society, including ideological and poetological ones and that there was no uniform way of defining or carrying out translations during the period under study. The findings also point at the segmentation of readership in early republican Turkey and conclude that the political and poetological factors governing the production and reception of translations varied for different segments of readers.
Keywords: Translating and interpreting.; Turkish literature -- Study and teaching.; Turkish literature -- Translations into English.